Correlation between SO2 with Acute Respiratory Infection in Surabaya City 2013–2015 - Firdaus, Aris Putra; Sulistyono, Lilis (JURNAL KESEHATAN LINGKUNGAN, 2018)
SO2 is an air pollutant and is one of the risk factors of ARI incidence. This research aims to identify the correlation between the levels of SO2 with ARI incidence in Surabaya City 2013–2015. Research on used ecologic study research design and used secondary data. The location selected on the basis of the research areas that have a ï¬ xed ambient air monitoring station SO2 levels that are still active. The location selected on location that has ï¬ xed ambient air monitoring station SO2 gas that is still active. Secondary data on SO2 levels measurement results taken from ï¬ xed ambient air monitoring station in Rungkut and Jambangan. While the ARI incidence secondary data taken at Puskesmas in Kecamatan Rungkut and Puskesmas in Jambangan. Air quality in the Surabaya City is still classiï¬ ed as good on level of SO2 (< 80 Î¼g/m3). The ARI incidence research in two locations during the 2013-2015 has decreased. There is a correlation between levels of SO2 with the ARI incidence, both in Rungkut district (correlation coefï¬ cient = 0.421, p = 0.036) and Jambangan district (correlation coefï¬ cient =-0.450, p = 0.024). SO2 levels are not the primary cause of ARI incidence. The ARI incidence can occur because other factors which are not examined namely indoor air pollution. Need for further research on correlation levels of SO2 in the outdoors and indoors with ARI incidence.